Introduction to nanocarbon biocomposites - Md Rezaur, Rahman; Muhammad Khusairy, Bakri; Murtala, Namakka (Elsevier Ltd., 2024)
Sawdust is a by-product of wood processing activities (Mallakpour et al., 2021), such as milling (Green et al., 1999), sawing (Mackes et al., 2001), and sanding generated by industries and agricultural activities (Bates & Davies, 2018; Boca & Miegroet, 2017; Gamfeldt et al., 2013; ˇ Kivinen et al., 2020; Rogers et al., 2020). It also consists of fine particles and shavings of wood that are generated as waste during these operations. Sawdust is typically dry, powdery, and lightweight. The size and texture of sawdust can vary depending on the type of wood being worked with and the cutting tools used. It may range from fine particles resembling dust to coarser shavings. Sawdust can be reused or repurposed in woodworking projects, such as using it as filler material or in wood-based composite products like particleboard (Bakri, 2018).